Features of the Relationship between Corruption, Human Capital Components and Economic Growth (Case of EU Candidate Countries) - Stryzhak, Olena (Ekonomika, 2025)
The changing geopolitical situation in the European region has actualized the issues of further EU enlargement. As a result, the relevance of studying many aspects of the functioning economic systems of candidate countries has increased. In this context, the purpose of this article is to identify the features of the relationship between economic growth, corruption, and human capital components in EU candidate countries. The study uses annual data for nine EU candidate countries from 1996 to 2021. The research methodology includes the following methods: correlation analysis; logarithm procedure; calculation of the Augmented Dickey-Fuller (ADF) test; calculation of the Granger causality test. The study found no causality in the cases of Albania, Bosnia and Herzegovina, North Macedonia, and Ukraine. The analysis showed that there is a causal relationship from Control of Corruption (CC) to GDP only in Moldova in the long term. In Montenegro, Serbia, and Turkiye, there is a causality from GDP and Life Expectancy at Birth (LEB) to CC. There is a direct causality from Education Index (EI) to GDP in Moldova, from LEB to EI in Georgia, and from LEB to GDP in Serbia and Montenegro. The study found differences in both the direction and strength of causality between components of human capital, control of corruption, and economic growth in the EU candidate countries. In some cases, there is no such relationship. All calculations were carried out using Statistica and EViews.